Pelatihan Olahraga Rugby untuk Menjaga Kesehatan di Bulan Ramadhan - Nur Salsabila Rhesa P. P.; Suryanto Agung Prabowo; Nurhasan Nurhasan (Jurnal Informasi Pengabdian Masyarakat, 2026)
The month of Ramadan often poses a challenge for college students to remain physically active due to changes in eating patterns and energy levels. This PKM program aims to design and implement a safe, effective, and fasting-friendly rugby training program for college students in East Java. Training sessions are scheduled at optimal times—after breaking the fast or before the pre-dawn meal—to uphold the practice of fasting without compromising physical fitness. The training materials were developed by experienced coaches and senior rugby players and include gentle warm-ups, light cardio exercises, basic rugby techniques, and effective cool-downs to prevent excessive fatigue. The program also features educational sessions on proper nutrition and hydration during Ramadan, including guidelines for iftar and suhoor to restore energy and maintain hydration. Beyond the physical aspects, this activity instills strong values of camaraderie and teamwork, strengthening social bonds among students from various faculties. It is hoped that this program will provide a valuable experience, raise awareness of the importance of an active lifestyle during Ramadan, and inspire students to stay healthy and enthusiastic while observing their fast.